2019
DOI: 10.1038/s41598-019-39789-9
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxy-D-Glucose inhibits aggressive triple-negative breast cancer cells by targeting glycolysis and the cancer stem cell phenotype

Abstract: Due to limited availability of pharmacological therapies, triple-negative breast cancer (TNBC) is the subtype with worst outcome. We hypothesised that 2-Deoxy-D-Glucose (2-DG), a glucose analogue, may hold potential as a therapy for particularly aggressive TNBC. We investigated 2-DG’s effects on TNBC cell line variants, Hs578T parental cells and their isogenic more aggressive Hs578Ts(i) 8 variant, using migration, invasion and anoikis assays. We assessed their bioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…There is conflicting evidence regarding the dependence of the CSCs of breast (and other tumor types) on glycolysis vs. oxidative phosphorylation. Reports have demonstrated that chemically inhibiting glycolysis reduces populations of breast cancer cells with CSC characteristics (35,36). Furthermore, during epithelial-mesenchymal transition (EMT), breast cancer cells undergo glycolytic metabolic reprogramming where they acquire CSC-like characteristics and exhibit increased tumorigenicity (37).…”
Section: Breast Cancer Stem Cells: Inherent Metabolic Plasticitymentioning
confidence: 99%
“…There is conflicting evidence regarding the dependence of the CSCs of breast (and other tumor types) on glycolysis vs. oxidative phosphorylation. Reports have demonstrated that chemically inhibiting glycolysis reduces populations of breast cancer cells with CSC characteristics (35,36). Furthermore, during epithelial-mesenchymal transition (EMT), breast cancer cells undergo glycolytic metabolic reprogramming where they acquire CSC-like characteristics and exhibit increased tumorigenicity (37).…”
Section: Breast Cancer Stem Cells: Inherent Metabolic Plasticitymentioning
confidence: 99%
“…Thus, combination of lower dose of 2-DG with other anticancer drugs, or with radiotherapy, is promising for clinical use (19). A recent report showed that 2-DG is also effective in inhibiting migration and invasion ability of an invasive subclone of the TNBC cell line, Hs578T (20). Due to limited therapeutic options for targeting metastasis, use of 2-DG for blocking cancer invasiveness is attractive, however, the study only showed the result of one BC cell line, Hs578T, and thus, further studies are required to clarify the role of glycolysis on BC invasion.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, we observed that 1 mM of 2-DG did not reduce cell survival of MDA-MB-231 and HCC1937 cell lines, but of note, it was signi cantly effective in blocking their invasion. Sadhbh O'Neill et al have reported that 2-DG is effective to inhibit migration and invasion ability of invasive BC subclone, Hs578T, but they used much higher concentration of 2-DG i.e., 15 mM (15 times the dose used in the current study), and have not focused on the effect of 2-DG with lower dose (20). The associated side effects of such a high dose of 2-DG would impede its use in clinical trials.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, combination of lower dose of 2-DG with other anticancer drugs, or with radiotherapy, is promising for clinical use (19). A recent report showed that 2-DG is also effective in inhibiting migration and invasion ability of an invasive subclone of the TNBC cell line, Hs578T (20). Due to limited therapeutic options for targeting metastasis, use of 2-DG for blocking cancer invasiveness is attractive.…”
mentioning
confidence: 99%